2014
DOI: 10.1186/1471-2407-14-951
|View full text |Cite
|
Sign up to set email alerts
|

High nuclear/cytoplasmic ratio of Cdk1 expression predicts poor prognosis in colorectal cancer patients

Abstract: BackgroundCdk1 (cyclin-dependent kinase 1) is critical regulator of the G2-M checkpoint. Cyclin-dependent kinase pathways are considered possible targets for cancer treatment; however, the prognostic role of Cdk1 in colorectal cancer is still controversial. Therefore, we attempted to determine the impact of Cdk1 on the clinical outcome of colorectal cancer patients to further identify its role in colorectal cancer.MethodsCdk1 immunoreactivity was analyzed by immunohistochemistry (IHC) in 164 cancer specimens f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
93
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 22 publications
(39 reference statements)
3
93
2
Order By: Relevance
“…Also, no differences were shown within the LSCC samples group when the N0 group was compared to N+ group. This is in contrast to findings from colorectal tumor when it has been shown that high nuclear/cytoplasmic ratio of CDK1 expression is connected with poor prognosis in this type of cancer [48]. …”
Section: Discussioncontrasting
confidence: 90%
“…Also, no differences were shown within the LSCC samples group when the N0 group was compared to N+ group. This is in contrast to findings from colorectal tumor when it has been shown that high nuclear/cytoplasmic ratio of CDK1 expression is connected with poor prognosis in this type of cancer [48]. …”
Section: Discussioncontrasting
confidence: 90%
“…It has been reported that Cdk1 expression or activity is elevated in Hodgkin's lymphomas [5], human colorectal cancer [6], prostate cancer [7], gastric lymphoma [8], childhood acute lymphoblastic leukemia [9] Therefore, Cdk1 is closely related with cancer progression. In particular, it has been reported that prognosis is poor in colorectal cancer patients with a high nuclear/cytoplasmic ratio of Cdk1 [6]. When activity of CDK1 and CDK2 was high in renal cell carcinoma patients, recurrence prediction rate was also high, while progression-free survival rate was low [10].…”
Section: Introductionmentioning
confidence: 99%
“…4 ( SIRT1, TGFBR1, CDK1 , and SMAD1 ) of the 15 genes were not present in any of the multi-tumor type cancer studies. All of the latter 4 genes contain cancer-related evidence232425262728293031, with SIRT1 and TGFBR1 also having documented genomic alterations293031 (Supplementary Note). …”
Section: Resultsmentioning
confidence: 99%